Book Reviews. Issue 1 (1st August 2019) - Ue, Tom; Naidu, Vayu
A Bond Undone: Legends of the Condor Heroes II, Jin Yong (trans. Gigi Chang) (2019) London: MacLehose Press-Quercus Publishing Ltd, 528 pp., ISBN 978-0-85705-461-6, p/bk, £14.99Chinatown Days, Rita Chowdhury (2018) New Delhi: Pan Macmillan Publishing India, 396 pp., ISBN 978-9-38621-523-9, h/bk, INR:599